2019
DOI: 10.1016/j.msea.2019.138352
|View full text |Cite
|
Sign up to set email alerts
|

Controlled cold rolling effect on microstructure and mechanical properties of Ce-modified SAF 2507 super duplex stainless steel

Abstract: Controlled cold rolling impacts on microstructure and mechanical properties of the rare earth Ce-modified SAF 2507 super duplex stainless steel (SDSS) are investigated towards a better application and development prospective over the pristine SDSS. Rolling was performed at room temperature with the deformation level in a range of 30% -90%. A large amount of dislocations into the ferrite phase turned out, and their density increased with the deformation. While, emergence of dislocation plugs group, ferrite grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 47 publications
1
9
1
1
Order By: Relevance
“…Compared to a scarcely reported cold rolling of SAF2507 (Zhou et al [12] ), the cryogenic deformation of the SDSS has not been reported in literature to the best of our knowledge. Aiming to a cost-effective processing and superior thermal processing performances, Ce-modified SAF2507 SDSS (Ce-SAF2507) with an increased N content is selected in the present study.…”
Section: Introductioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Compared to a scarcely reported cold rolling of SAF2507 (Zhou et al [12] ), the cryogenic deformation of the SDSS has not been reported in literature to the best of our knowledge. Aiming to a cost-effective processing and superior thermal processing performances, Ce-modified SAF2507 SDSS (Ce-SAF2507) with an increased N content is selected in the present study.…”
Section: Introductioncontrasting
confidence: 75%
“…Furthermore, comparison of strain analysis for cold (Zhou et al [ 12 ] ) and cryogenically rolled Ce‐SAF2507 shows similar trends, i.e., increase in strain with the deformation level. However, it is important to note that the strain accumulation of ferrite is lower (20 × 10 −4 ) than that of the room‐temperature cold rolling (52 × 10 −4 ), which is rather intriguing.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This is because ferrite’s stacking fault energy is higher than austenite’s. In the process of surface plastic deformation, a large number of dislocations are more likely to form in ferrite, resulting in dislocation proliferation and entanglement [ 30 , 31 ]. Dislocation densities of ferrite and austenite were lower in specimen 4 than in specimen 1.…”
Section: Resultsmentioning
confidence: 99%